Analisis Perbedaan Rata-rata Pendapatan Pedagang Acung Pinggir Pantai di Kecamatan Kuta Kabupaten Badung - Arsana Putra, I Gede Susila; Setyadhi Mustika, Made Dwi (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
The existence and contribution of tourism sector make the multiflier effect to the Bali’s economy by improve the informal sectors development. This research objected to know the demography social characteristic of side shore vendors, and to analyze the disparity of side shore vendors at Kuta Beach and Legian Beach. This reseach used 70 sampels its kind of 35 sampel for each locations. The result showed : 1) most vendors are men about 35-44 years; 2) dominantly, vendors come from Bali outside Badung Region, that primary school graduated, and they have been selling about 5-9 years; 3) most of them are married, whose children are about 1-2; 4) the Mann-Whitney Test resulted Z table (-1,96) > Z hitung (-2,8), that implied there is an average differenciacy of income  to the vendors at Kuta Beach and Legian Beach. Based on those things, the writer suggested that it is needed cooperation and serious efforts from the government of Badung Region and the related SKPD to make the vendors well organized.
Keywords: average diffrenciacy; income; torism sector; vendors